Desain dan Implementasi Pengaturan Kecepatan Motor BLDC Melalui Pengaturan Fluks - Ony Asrarul Qudsi; Syechu Dwitya Nugraha (INOVTEK - Seri Elektro, 2019)
This journal presents the design and implementation of BLDC motor speed control. Speed control of the BLDC motor can be done by controlling the flux produced by the BLDC motor coil. The current reading by the sensor will be processed in the flux estimator to get the flux value in the motor. By using the PI controller, the flux value generated by the coil will be controlled so that it is equal to the setpoint value that has been determined. Flux values that have the same setpoint will be converted to PWM values which will be used as input signals on the six step inverter. The test results by providing disturbance form the additional load on the motor, shows that the motor is able to maintain its speed according to the value of the speed provided. Thus, the proposed speed regulation method can work well.